뇌졸중 환자를 대상으로 실시한 한글판 기능적 보행평가의 타당도 - 박소연; So Yeon Park (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2016)
Background: The Functional Gait Assessment (FGA) was developed to measure of gait-related activities. The FGA was translated in Korean but only a few psychometric characteristics had been studied. Objects: The purpose of this study was to evaluate the validity and reliability of the Korean version of FGA scale using Rasch analysis. Methods: The study included 120 patients with stroke (age range=30~83 years; mean±standard deviation=58.3±11.1). The FGA and Berg Balance Scale were performed, and were analysed for dimensionality of the scale, item difficulty, scale reliability and separation, and item-person map using Rasch analysis. Results: The 4 rating scale categories of FGA were satisfied with optimal rating scale criteria. The most items of the FGA showed sound item psychometric properties except 2 items (‘gait with the horizontal head turns’, and ‘gait with narrow base of support’), and the 2 misfit items were excluded for all further analyses. The 8 items were arranged in order of difficulty. The most difficult item was ‘gait with eyes closed’, the middle difficult item was ‘gait level surface’, and the easiest item was ‘gait with vertical head turns.’ A person separation reliability was .93 and the person separation index was 3.57. Conclusion: This study suggests that the 8-item Korean FGA are valid measure of assess the gait-related balance performance, and to set the goal of rehabilitation plan in patient with stroke.